Historiography of Coastal Communities in Indonesia - Endang Susilowati (Journal of Maritime Studies and National Integration, 2019)
This article examines the development of the historiography of coastal communities in Indonesia and suggested interesting themes that can be developed. A contradictory situation in which Indonesia as a great maritime nation with a large number of coastal villages where tens of millions of people live in, dominantly they are fishing communities and sea tribes. However, historiography about coastal communities is still a few in number. To date, the historiography of Indonesia’s maritime focuses more on sailing, trading, and port activities. The historiography of coastal communities as a part of maritime history studies has not been widely conducted. A published dissertation by Masyhuri (1996) on the socio-economic lives of fishermen on the north coast of Java became the first study on the lives of coastal communities in Indonesia. Several other studies such as the study conducted by Widodo (2005), Kesuma (2004), Alimuddin (2005), Vickers (2009), Hamid (2011) and Suyuti (2011) are some examples of the historiography of coastal communities. Through the bibliographical study, it is found that the lack of historiography of coastal communities due to limited written sources because of the absence of writing tradition among these communities. However, along with the development of historical methodology, historical sources are no longer dependent solely on written sources, thus studies on the historiography of coastal communities have started to be carried out.